2004
DOI: 10.1158/0008-5472.can-03-4080
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Interacts with and Is Required for Paclitaxel-Induced Activation of Mitogen-Activated Protein Kinase Kinase Kinase 3

Abstract: BRCA1 has been implicated in a number of cellular processes, including transcriptional regulation, DNA damage repair, cell cycle arrest, and apoptosis. We identified mitogen-activated protein kinase (MAPK) kinase kinase 3 (MEKK3), an upstream regulator of the c-Jun NH 2 -terminal kinase/stress-activated protein kinase and p38/MAPK pathways, as a novel BRCA1-interacting protein in a yeast two-hybrid screen and confirmed the interaction by coimmunoprecipitation in mammalian cells. Deletion mapping demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…It is not known at present how BRCA1 enhances spindle arrest in response to these drugs but this may be due in part to its association with and subsequent activation of MEKK3 following microtubule damage (Gilmore et al, 2004). We previously demonstrated that inducible expression of GADD45 also activated the G2/M checkpoint in response to microtubule agents, suggesting that BRCA1-mediated transactivation of GADD45 may be important in the regulation of the mitotic checkpoint (Mullan et al, 2001).…”
Section: Mitotic Checkpointmentioning
confidence: 99%
“…It is not known at present how BRCA1 enhances spindle arrest in response to these drugs but this may be due in part to its association with and subsequent activation of MEKK3 following microtubule damage (Gilmore et al, 2004). We previously demonstrated that inducible expression of GADD45 also activated the G2/M checkpoint in response to microtubule agents, suggesting that BRCA1-mediated transactivation of GADD45 may be important in the regulation of the mitotic checkpoint (Mullan et al, 2001).…”
Section: Mitotic Checkpointmentioning
confidence: 99%
“…The gene is involved in a variety of cellular processes, including apoptosis [23,24] . Quinn et al [24] found that the presence of BRCA1 causes breast cancer cells to undergo enhanced levels of apoptosis by mitotic-spindle-poisoning agents such as paclitaxel.…”
Section: Synergistic Interaction Between Paclitaxel and Zoledronic Acmentioning
confidence: 99%
“…Proinflammatory cytokines, including IFN-g, IL-1, and tumor necrosis factor-a, have been shown to activate MEKK1 or MEKK3 (40)(41)(42). In addition, MEKK3 activation has been linked to paclitaxel-induced, BRCA1-dependent apoptosis in breast cancer (43) and to TRAF7-mediated apoptosis (44) and MEKK3 has been shown to physically interact with BRCA1 and TRAF7. Although we have not been able to successfully measure MEKK kinase activity in our system, we did find that MEKK1, MEKK2, and MEKK3 were expressed in all three cell lines, and the degree of expression was not altered by either IFN-g or IFN-a.…”
Section: Effects Of Ifn-mentioning
confidence: 99%